NILAI- NILAI PENDIDIKAN ISLAM DALAM TRADISI BUBAK KAWAH DI DESA MOROSARI PONOROGO - Syamsul Muqorrobin; Tamrin Fathoni; Asfahani Asfahani (Pendidikan Agama Islam, 2020)
This study aims to describe the values ​​of Islamic education in the tradition of Bubak Kawah in Morosari Village. The method used is descriptive-qualitative. From the research conducted found that The first value of Islamic education is gratitude to God from the parents of the bride because of God's grace, her child is given the ease to find her soul mate. The second value of Islamic education is the request to God that the bride be given strength, physical and spiritual freshness. The third educational value is can be seen from the various equipment used in the Bubak Kawah event